Pengaruh Label Halal dan Citra Merek terhadap Keputusan Pembelian dengan Ekspektasi sebagai Variabel Mediasi: (Studi pada Konsumen Ichiban Sushi Mall Ciputra Semarang) - Nisrina, Ghina; Felda, Elina; Nurhayati; Firdaus; Fahmi, Ahmad; Isna, Nova (Prodi Administrasi Bisnis FISIP Universitas Tulang Bawang Lampung, 2024)
The aim of this research is to determine the influence of the halal label and brand image on purchasing decisions for Ichiban Sushi products. This research uses the halal label and brand image as independent variables and uses purchasing decisions as the dependent variable which is mediated by expectations. The population for this research is consumers or visitors to Sushi Mall Ciputra Semarang and the sample size is 100 respondents. The sampling technique for this research is purposive sampling. Data collection uses a questionnaire with a Likert scale of 1-5. The data analysis method used is mediation path analysis and hypothesis testing in this research using Macro PROCESS Hayes in SPSS 22 for Windows. The results of this research show that (1) There is an influence of the halal label on expectations (2) There is an influence of brand image on expectations (3) There is an influence of expectations on purchasing decisions (4) Expectations significantly mediate the influence of the halal label on purchasing decisions Keywords: halal label, brand image, expectations, purchase decisions